The global status of research in prostate cancer bone metastasis: A bibliometric and visualized analysis - Lv, Zongwei; Wang, Xia; Zhu, Chunming; Wang, Kefeng (Frontiers in Medicine, 2022)
Background Prostate cancer (PCa) is a serious threat to the health of elderly aged groups. It is very important to understand the occurrence and development of PCa for early diagnosis, treatment and metastasis control. This study aims to elucidate the international frontier research direction and literature distribution through bibliometric and visual analyses of PCa bone metastasis. Methods Data were obtained from the Web of Science core collection database, which collected 2,246 papers related to PCa bone metastasis from 1 January 2012 to 31 December 2021. The collected data were analyzed using the VOSviewer software for citation, co-authorship, co-citation, bibliometric coupling, and co-occurrence. Results Over the past decade, published papers have increased annually. The United States of America has published 890 papers with 29,161 citations, far more than any other country, and it has the most extensive collaboration with other countries. For example, 33 articles by Saad Fred were cited 2,721 times, and 91 articles from the University of Texas MD Anderson CANC CTR were cited 3,037 times, the most cited author and organization. Peng Xinsheng and Duke UNIV comprise the most active collaborative author and organization, respectively. The most co-cited journal was CANCER RES, with 3,195 citations. Studies of PCa bone metastasis can be divided into four categories: “basic research,” “auxiliary diagnosis and treatment,” “clinical trial,” and “prognosis.” Conclusion Our results provide a comprehensive overview of the research priorities and future directions of PCa bone metastasis, which can further accurately guide researchers in diagnosis, treatment, and personalized prevention.